
把下列各式分解因式:(1)(m-n)^3-(m-n)^2 (2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a)
把下列各式分解因式:(1)(m-n)^3-(m-n)^2(2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a)...
把下列各式分解因式:
(1)(m-n)^3-(m-n)^2
(2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a) 展开
(1)(m-n)^3-(m-n)^2
(2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a) 展开
1个回答
展开全部
(1)(m-n)^3-(m-n)^2
=(m-n)²(m-n-1)
(2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a)
=(3a-4b)(7a-8b)-(11a+2b)(7a-8b)
=(7a-8b)(3a-4b-11a-2b)
=-2(7a-8b)(4a+3b)
=(m-n)²(m-n-1)
(2)(3a-4b)(7a-8b)+(11a+2b)(8b-7a)
=(3a-4b)(7a-8b)-(11a+2b)(7a-8b)
=(7a-8b)(3a-4b-11a-2b)
=-2(7a-8b)(4a+3b)
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询